Factoring Trinomials Formula

Factoring Trinomials Formula

Polynomial expression in the form of

\(\begin{array}{l}ax^{2}+bx+c\end{array} \)
is known as a Trinomial.

\(\begin{array}{l}\large a^{2} + 2ab + b^{2} = (a+b)^{2}\end{array} \)

\(\begin{array}{l}\large a^{2} – 2ab + b^{2} = (a-b)^{2}\end{array} \)

\(\begin{array}{l}\large a^{2} – b^{2} = (a+b)(a-b)\end{array} \)
\(\begin{array}{l}\large a ^{3} + b ^{3} = (a + b) (a ^{2} – a b + b ^{2})\end{array} \)

\(\begin{array}{l}\large a ^{3} – b ^{3} = (a – b) (a ^{2} + a b + b ^{2})\end{array} \)

Solved Examples

Question 1: Factor 

\(\begin{array}{l}2 x ^{2} – 5 x – 12\end{array} \)
.

Solution:

\(\begin{array}{l}2 x ^{2} – 5 x – 12\end{array} \)

=

\(\begin{array}{l}2 x^{2} + 3x – 8x – 12\end{array} \)

=

\(\begin{array}{l}x (2x + 3) – 4 (2x + 3)\end{array} \)

=

\(\begin{array}{l}(2x + 3) (x – 4)\end{array} \)

Leave a Comment

Your Mobile number and Email id will not be published.

*

*